PERFORMANCE ANALYSIS OF 20WP SOLAR PANEL AS A SOURCE OF ENERGY IN AUTOMATIC SINK - Tharo, Zuraidah; Hamdani, Hamdani; Andriana, Melly; Andhika, Putra (Proceeding International Conference of Science Technology and Social Humanities, 2022)
Short-term and long-term energy needs and consumption in the supply and utilization of sustainable energy nationally, require direction and strategic steps to achieve. Fossil energy, which has been the mainstay of energy consumption, has had an impact on the depletion of non-renewable natural resources and increasing environmental damage. This encourages the emergence of various calls to reduce and limit the use of fossil energy and replace it with Renewable Energy. Solar energy is a source of energy that is widely available in nature and is relatively easy to use. Many innovations are made by utilizing sunlight, one of the innovations is by utilizing sunlight as an energy source in an automatic sink. With a 20 Wp solar panel, it can generate electricity of 150.66 Wh/day. This amount can supply an automatic sink which requires 81.18 Wh/day of energy. By carrying out a simple design and calculations and tests in order to obtain an innovation in the use of Renewable Energy.